2017
DOI: 10.20473/jbe.v5i1.2017.26-36
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Related With Diptheria Cases of Children in Bangkalan Health Centers in 2016

Abstract: The diptheria cases raised up in Bangkalan District in 2015, as many as 19 case with CFR 15,79% spread in 13 subdistricts/villages. This study was to analyze the risk factors the corelated factors to dipheria cases of children with case control design and analyses data using computer computing. It condusted in July-December 2016 by using questionnaire, interviews, observation, and measurement. Total sample was 48 respondents which number of case 8 respondents and number of control 40 respondents. Variabel in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
3
3
0
1
Order By: Relevance
“…Number of boys were more Clinical Manifestation of Childhood Diphtheria Geune Putroe Zulfan, Jumaini Adriana Sihombin, Desrinawati Muhammad Amin, Aninda Dinar Widiantari, Monalisa Putri Eka Berti, Farida Murtiani than girls in our study. This finding was in line to result of (Arifin & Prasasti, 2017)'s research that pointed boys were more prone to get infected due to their outdoor activity that lead to bigger exposure to the disease. It was also supported by two other studies, (Arya et al, 2022) and (Harsanti et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Number of boys were more Clinical Manifestation of Childhood Diphtheria Geune Putroe Zulfan, Jumaini Adriana Sihombin, Desrinawati Muhammad Amin, Aninda Dinar Widiantari, Monalisa Putri Eka Berti, Farida Murtiani than girls in our study. This finding was in line to result of (Arifin & Prasasti, 2017)'s research that pointed boys were more prone to get infected due to their outdoor activity that lead to bigger exposure to the disease. It was also supported by two other studies, (Arya et al, 2022) and (Harsanti et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Booster immunization program commenced in 2016, therefore many people did not know the importance of immunization. It is congruent with the research by Arifin & Prasasti (2017) that stated the provision of three doses of DPT with one repeated dose may affect the effectiveness of vaccination. Giving a complete DPT will be more effective in protecting a person from diphtheria.…”
Section: The Status Of Diphtheria Immunization Patients In East Java Provincesupporting
confidence: 86%
“…The low immunity is align to the age. It is in line with the research by Arifin & Prasasti (2017) which sated that the absence of diphtheria immunization will put the children at risk of getting diphtheria more easily. In addition, the children unimmunized will have lower immunity than the children who have been diphtheria immunized.…”
Section: The Status Of Diphtheria Immunization Patients In East Java Provincesupporting
confidence: 83%
See 1 more Smart Citation
“…Several studies have shown that low vaccination coverage, crowding and migration, or a combination of host, agent, and environmental factors, can influence the incidence of diphtheria 6, 7 . Other factors include nutritional status and parental behavior, personal hygiene of children 8 , density of house occupancy, humidity in the house, type of floor of the house and the source of transmission (contracting from other people), parents knowledge about diphtheria 9 , parent education level 10, 11 , child age, home lighting, and house ventilation 12 .…”
Section: Introductionmentioning
confidence: 99%